Technological innovations and workplace automation potential - Drnda, Adnan (2017)
This thesis examines key technologies of ongoing technological revolution and its potential impact on workplace automation. First, the importance of technological innovations throughout history is presented. Second, using the systematic review of relevant sources, the following seven most important technology trends are identified and their comprehensive overview is provided: Artificial Intelligence, Cloud Computing, Internet of Things, (Big) Data Analytics, Virtual and Augmented Reality, Advanced Robotics and Blockchain. Third, capabilities of currently available technologies and their potential to substitute human labor are described. Fourth, an overview of selected studies focusing on estimating automation potential for specific occupations is provided. Finally, a case study estimating automation potential for 33 back-office employees working for a Czech IT company is conducted. The results point out to the existence of a significant automation potential ranging between 24% and 69% for individual back-office positions.